Commentaries on the IMIA Award of Excellence Lecture by Reinhold Haux - Hasman, A.; Hersh, W.; Lorenzi, N. M.; Shortliffe, E. H.; van Bemmel, J. H. (Yearbook of Medical Informatics, 2014)
The IMIA Yearbook editorial team asked five internationally renowned biomedical informaticians to respond to Prof. Haux’s editorial. This paper summarizes their thoughts and responses. Contributions are ordered alphabetically by the contributor’s last name. All authors provided an equal contribution to this manuscript.